Cervical screening in Perth and Kinross since introduction of the new contract. - Reid, G S (1991)
OBJECTIVE--To determine changes in the cervical screening service since the introduction of the new general practitioner contract on 1 April 1990. DESIGN--Analysis of computerised records of cervical screening both before and after introduction of the new contract. SETTING--General practices in Perth and Kinross Unit, Tayside. PATIENTS--A total of 30,071 women aged 21-60 on 26 general practitioner partnership lists. MAIN OUTCOME MEASURES--Percentage average of target population for cervical screening in each practice for first three quarters on introduction of the contract. RESULTS--Perth and Kinross Unit completed a computerised cervical screening call programme in July 1989, which produced an increase from 71% to 78% in the mean percentage of women aged 20-60 who had had cervical smear tests within 5.5 years. Six months after the introduction of the new general practitioner contract the mean population coverage was increased to 85% in women aged 21-60 and only four practices had not attained the 80% upper target compared with 10 on 1 April 1990. Detailed examination of randomly selected practices immediately before the new contract was introduced showed an average artificial list inflation of 4.3% in health board records when compared with practice records, a hysterectomy rate of 6.2%, and an additional 3% of women who were considered to be ineligible for smear testing due to putative virginity or illness or infirmity, or both. There was a considerable shift away from use of well woman clinics (2.7% of smears in 1990 compared with 5.6% in 1988) for taking cervical smears, potentially threatening the long term viability of the clinics. CONCLUSION--The introduction of the new contract for general practitioners has brought about a further sustained increase in population coverage for cervical screening in a small Scottish unit with a stable population, well motivated general practitioners, and a fully integrated computerised call and recall system based on the community health index. To optimise the screening service revision of the targets levels is necessary.